Travel intention and Behavioral Changes during COVID-19 Pandemic: Empirical Implication for the Travel and Tourism Industry - Gaonkar, Sadanand (Turizam, 2022)
The COVID-19 outbreak has miserably disrupted the tourism industry and travelling lifestyle of people. Since the outbreak is not yet over it is presumed that the intention and behavior of people towards travelling will change. Thus, in this context, the study employs an empirical research to examines the travel intentions of travellers during COVID-19 pandemic and identifies the behavioral changes that traveller’s may have experienced while visiting any destination during the pandemic. For this purpose, a primary data was collected from 121 travellers randomly and analyzed using descriptive statistics, regression analysis, ANOVA, paired and independent sample t-test. The result indicates that the travel intentions of the respondents are influenced by perceived behavioral control. It is also revealed that the respondents will only choose such destinations that have taken all the precautionary measures. The study concludes that COVID-19 pandemic has significantly influenced the travel behavior of travellers.
Keywords: behavior; COVID-19; intentions; pandemic; travel; travellers